The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.bcp.2015.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine modulation of fear memories and anxiety: Implications for learning and anxiety disorders

Abstract: Anxiety disorders are a group of crippling mental diseases affecting millions of Americans with a 30% lifetime prevalence and costs associated with healthcare of $42.3 billion. While anxiety disorders show high levels of co-morbidity with smoking (45.3% vs. 22.5% in healthy individuals), anxiety disorders are also more common among the smoking population (22% vs. 11.1% in the non-smoking population). Moreover, there is clear evidence that smoking modulates symptom severity in patients with anxiety disorders. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 253 publications
(251 reference statements)
0
58
0
2
Order By: Relevance
“…While the increase in nicotine consumption can be explained by its anxiolytic properties (Ericson et al, 2000; O’Neill and Brioni, 1994), there is also evidence suggesting that nicotine may aggravate PTSD symptomatology as studies found that nicotine intake increased trauma-related intrusive memories (Hawkins and Cougle, 2013) and fear response to trauma-related scripts (Calhoun et al, 2011). In line with human studies, studies using animal models of fear learning have also shown that nicotine alters fear memory (see Kutlu and Gould, 2015 for a review). These studies repeatedly demonstrated that acute nicotine selectively enhanced hippocampus-dependent forms of fear conditioning, such as contextual and trace fear conditioning, but does not affect hippocampus-independent cued fear conditioning (Gould and Wehner, 1999; Gould, 2003; Gould and Stephen Higgins, 2003; Gould and Lommock, 2003; Gould et al, 2004; Davis et al, 2005, 2006; Davis and Gould, 2006).…”
Section: Introductionmentioning
confidence: 73%
“…While the increase in nicotine consumption can be explained by its anxiolytic properties (Ericson et al, 2000; O’Neill and Brioni, 1994), there is also evidence suggesting that nicotine may aggravate PTSD symptomatology as studies found that nicotine intake increased trauma-related intrusive memories (Hawkins and Cougle, 2013) and fear response to trauma-related scripts (Calhoun et al, 2011). In line with human studies, studies using animal models of fear learning have also shown that nicotine alters fear memory (see Kutlu and Gould, 2015 for a review). These studies repeatedly demonstrated that acute nicotine selectively enhanced hippocampus-dependent forms of fear conditioning, such as contextual and trace fear conditioning, but does not affect hippocampus-independent cued fear conditioning (Gould and Wehner, 1999; Gould, 2003; Gould and Stephen Higgins, 2003; Gould and Lommock, 2003; Gould et al, 2004; Davis et al, 2005, 2006; Davis and Gould, 2006).…”
Section: Introductionmentioning
confidence: 73%
“…In contrast, anxiogenic effects of nicotine withdrawal are enhanced by stimulation of α7 nAChRs and decreased by inhibition of these nAChRs receptors (Kutlu and Gould, 2015). Allosteric modulation of α4β2 nAChRs by dFBr did not affect anxiety-like behavior in the OF test in the BIG mice, suggesting that these nAChRs receptors may not be involved in the control of anxiety in nicotine-naïve mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is evidence showing that acute nicotine intake increases the likelihood of intrusive traumatic memories in healthy nonsmokers (Hawkins and Cougle 2013). Moreover, evidence from multiple animal studies showed that acute nicotine enhances contextual fear learning (Gould and Higgins 2003;Gould and Lommock 2003;Davis et al 2006) and disrupts extinction of fear memories Kutlu et al 2016; for review, see Kutlu and Gould 2015). Therefore, given the higher rates of smoking initiation in PTSD patients, the period of acute nicotine intake following a traumatic event may be especially critical for the development and relapse of fear in PTSD.…”
mentioning
confidence: 99%